Nina Rodrigues: as relações entre mestiçagem e eugenia na formação do povo brasileiro - Neves, Márcia das (2008)
The aim of this dissertation is to study the views of the Brazilian physician Raimundo Nina Rodrigues concerning the human races and the role of the crossing between different races in the constitution of the Brazilian people. It will try to check to what extent they were well grounded on the scientific knowledge of his time. This dissertation contains an introduction and four chapters. Chapter 1 presents an overview of the historical, social and scientific context of Nina Rodrigues time and his main contributions. Chapter 2 discusses Nina Rodrigues ideas concerning the human races, comparing them to the views which were generally adopted by other authors of his time. Chapter 3 analyses Nina Rodrigues views about the role of the crossing of different breeds in the constitution of the Brazilian people. Chapter 4 attempts to answer to the questions presented in the Introduction and makes some final remarks on the subject. Nina Rodrigues classification of human races (white, black and red) was different from the one which was adopted by most medical works of his time. He considered that some breeds were inferior to others, and that the same occurred in the case of crossbreds. Concerning the crossing between different races, he considered it as being harmful, except in the cases when it could bring back the characters of the purest race (white). In the different works he published during his life, he did not soften his views concerning the role of crossings between different races. This research led to the conclusion that Nina Rodrigues, in general, was not concerned in providing a foundation for his ideas related to the superiority/inferiority of races, or about crossbreds. His way of dealing with the issue of the composition of the Brazilian people, arguing for its whitening a view that was also advocated by the Brazilian elite was loaded with preconceptions and it was almost completely devoid of any foundation as regards the scientific knowledge of that time